Deteksi Odontoglossum ringspot virus Terhadap Anggrek Alam di Hutan Wonosadi, Gunung Kidul - Mahfut K; Budi Setiadi Daryono (Biogenesis: Jurnal Ilmiah Biologi, 2014)
Wonosadi forest is managed forests by indigenous forest communities and is located in the hamlet of Duren and Sidorejo, Beji village, subdistrict Ngawen, Gunung Kidul regency, Yogyakarta. One of the biological richness contained in Wonosadi forest is very valuable natural orchids and need to be preserved. Management to the preservation of nature in the woods Wonosadi orchids can be done through natural orchid protection against infectious pathogens, including viruses. Odontoglossum ringspot virus (ORSV) is one type of orchid viruses infect most widely reported and has spread widely in the world, including in Indonesia. ORSV can cause severe damage to the orchid. Therefore, it is necessary to study to detect ORSV that infect wild orchids in the forest Wonosadi molecular basis for detecting the presence and pattern of infection ORSV as well as possible to reduce the severity of disease caused by infection with the virus. The purpose of this study is to assess the natural orchid ORSV infection in molecular Wonosadi forest that can be used as a database in an effort to protect against natural orchid Wonosadi forest. In the long term, the results of this study are very useful to support conservation efforts and determine appropriate conservation efforts for wild orchids in the forest Wonosadi. The initial phase of the study conducted a survey and collection of samples of wild orchids in the forest leaves that show symptoms of infection Wonosadi ORSV. Furthermore, molecular analysis performed with gene amplification Coat Protein ORSV using Reverse engineering Trancriptase Polymerase Chain Reaction (RT-PCR).Keywords: orchid soil, ORSV, RT-PCR, Wonosadi forest